Enhanced antitumor effect on intrapulmonary tumors of docetaxel lung-targeted liposomes in a rabbit model of VX2 orthotopic lung cancer - Wang, LiJuan (Sci Rep, 2017)
Allergic reactions and severe systemic toxicity are two major challenges for the clinical application of docetaxel (DTX) for treatment of non-small-cell lung cancer (NSCLC). We developed a novel lung-targeted DTX-loaded liposome (DTX-LP), an efficient drug delivery system, with a patented DBaumNC technology to overcome these deficiencies. In the present study, we describe the targeting activity, tumor inhibition rate (TIR), survival, pathology, tumor apoptosis and metabolism of DTX after intravenous injection of DTX-LP compared to the DTX injection (DTX-IN) formulation based on the VX2 orthotopic lung cancer rabbit model. Biodistribution studies revealed the highest accumulation in lung and tumor within 12 h after the injection of DTX-LP. The increased TIR indicates that the growth of tumor was slowed. Pathology tests demonstrated that DTX-LP can reduce metastasis and toxicity to non-targeted organs, leading to greatly extended survival time and improved survival of tumor-bearing rabbits. Flow cytometry and immunohistochemistry confirmed that DTX-LP is highly efficacious in tumor tissue, leading to a significant increase of tumor apoptosis and decrease of proliferation and angiogenesis. The results from this study demonstrate the increased intrapulmonary tumor targeting activity, enhanced antitumor effect and reduced toxicity of DTX-LP compared to DTX-IN and highlight its clinical prospects for NSCLC therapy.